ASSESSMENT OF PERSONNEL NEEDS FOR INPATIENT NURSES AT RSI A.YANI SURABAYA USING THE WISN METHOD - Sari, Dini Kharisma; Budhi Setianto; Chalidyanto, Djazuli (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
Nursing staff is a priority in providing services to patients. If the number of nurses and patients is not balanced, this will result in workload problems and the lack of staff will result in less than optimal service to patients. In this study, the method used to calculate staffing needs was WISN (Workload Indicators of Staffing Need) for Mekkah inpatient nurses (adult inpatients). The WISN method has five stages: finding available work time, finding work units and human resources categories, making work load standards, making allowance standards, and calculating labor requirements for each work unit. The aim is to analyze the need for nursing staff based on the workload in the Mekkah inpatient unit (adult inpatient unit). The time motion study method is to be able to understand more deeply the phenomena that occur and are felt by the informants through observations and interviews. The results of research on staff requirements using the WISN method were 35 nurses with real conditions of 20 nurses so there was a shortage of 10 nurses.